Communication and Behavior Change in Rice Farmers’ Pest Management: The Case of Using Mass Media In Vietnam - M. M. Escalada; K. L. Heong; N. H. Huan; V. Mai (Journal of Applied Communications, 1999)
Rice farmers’ unnecessary insecticide use for leaf folder control is due to misperceptions. A mass media campaign was organized to motivate farmers to test a conflict information expressed as a heuristic. After the campaign, insecticide use dropped from 3.35 sprays per farmer to 1.56. Proportions of farmers spraying at the early and late tillering and booting stages decreased from 59%, 84% and 85% to 0.2%, 19% and 30%, respectively. Leaf folder control perceptions, expressed as the belief index, changed from 11.25 to 7.62. Proportions of farmers believing that leaf folders could cause damages, yield loss and needed sprays, dropped from 66%, 70% and 77% to 24%, 25% and 23%, respectively. The study showed that mass media could effectively transfer some elements of knowledge-intensive pest management, especially simple non-site specific information designed to motivate.